2015
DOI: 10.1002/job.2044
|View full text |Cite
|
Sign up to set email alerts
|

Religious harassment in the workplace: An examination of observer intervention

Abstract: Religious harassment claims in the United States have risen sharply over the past decade. However, victims of religious harassment may not always report harassment, and true rates may be higher. Hence, actions taken by third parties present (observers) are important in combating harassment in the workplace. The purpose of this paper is to extend a previous model of observer intervention and related research by testing it empirically in the context of religious harassment and identify factors that influence obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…Bowes-Sperry and O’Leary-Kelly (2005) adapted and expanded on Latané and Darley’s (1970) model to predict that intervention is also contingent upon (a) the ambiguity and severity of vicarious mistreatment, (b) other observers’ reactions to vicarious mistreatment, (c) the relationship between the victim and the perpetrator, (d) the third party’s organizational role, and (e) whether the third party and victim share a social identity. A number of the components of this model have been empirically upheld; bystanders have been found to be most likely to take action when the mistreatment event was unambiguous (Espinoza & Cunningham, 2010; Ghumman, Ryan, & Park, 2016; Ryan & Wessel, 2012), victim consequences were higher rather than lower in severity (Bowes-Sperry & Powell, 1999; Hellemans, Dal Cason, & Casini, 2017), the third party believed other bystanders would view the behavior as inappropriate (Bowes-Sperry & Powell, 1999), there was a professional rather than personal relationship between the victim and the perpetrator (Chui & Dietz, 2014), and the witness occupied a role with more responsibility to report mistreatment (Holland et al, 2016). Though studies have not supported shared social identity as a predictor of intervening (Bowes-Sperry & Powell, 1999; Ghumman et al, 2016), third parties were found to be more likely to intervene when they had a closer relationship with the victim (Coyne, Gopaul, Campbell, Pankász, Garland, & Cousans, in press; Ghumman et al, 2016; Ryan & Wessel, 2012), suggesting that interconnectedness between the victim and the third party does influence bystander intervention.…”
Section: Consequences Of Vicarious Mistreatmentmentioning
confidence: 99%
“…Bowes-Sperry and O’Leary-Kelly (2005) adapted and expanded on Latané and Darley’s (1970) model to predict that intervention is also contingent upon (a) the ambiguity and severity of vicarious mistreatment, (b) other observers’ reactions to vicarious mistreatment, (c) the relationship between the victim and the perpetrator, (d) the third party’s organizational role, and (e) whether the third party and victim share a social identity. A number of the components of this model have been empirically upheld; bystanders have been found to be most likely to take action when the mistreatment event was unambiguous (Espinoza & Cunningham, 2010; Ghumman, Ryan, & Park, 2016; Ryan & Wessel, 2012), victim consequences were higher rather than lower in severity (Bowes-Sperry & Powell, 1999; Hellemans, Dal Cason, & Casini, 2017), the third party believed other bystanders would view the behavior as inappropriate (Bowes-Sperry & Powell, 1999), there was a professional rather than personal relationship between the victim and the perpetrator (Chui & Dietz, 2014), and the witness occupied a role with more responsibility to report mistreatment (Holland et al, 2016). Though studies have not supported shared social identity as a predictor of intervening (Bowes-Sperry & Powell, 1999; Ghumman et al, 2016), third parties were found to be more likely to intervene when they had a closer relationship with the victim (Coyne, Gopaul, Campbell, Pankász, Garland, & Cousans, in press; Ghumman et al, 2016; Ryan & Wessel, 2012), suggesting that interconnectedness between the victim and the third party does influence bystander intervention.…”
Section: Consequences Of Vicarious Mistreatmentmentioning
confidence: 99%
“…Employees may be unaware of their tendencies to treat persons from minority communities unfairly, or that their attitudes toward people from distinct demographic backgrounds could be negative. Organizational decision-makers might harbor unconscious biases regarding individuals from identifiable subgroups or minority communities and thus potentially act negatively toward these individuals (e.g., Ghumman et al, 2016;Hebl et al, 2002; State of New South Wales, Department of Premier and Cabinet, Behavioral Insights Unit, 2016). Unconscious biases among organizational decision-makers might limit promotion or participation of minority individuals in leadership roles.…”
Section: Does Anti-harassment or Anti-racial Discrimination Training mentioning
confidence: 99%
“…Identity is core to diversity in the workplace reflecting fundamental social differences among people. Workplace diversity entails more than visible or surface‐level diversity (e.g., age or ethnicity), but also the deep‐level diversity associated with sexual orientation, class, or, indeed, religion (e.g., Ghumman, Ryan, & Park, ; Harris & Yancey, ). Although some religious identities can be invisible to coworkers, others have visible signifiers, such as the wearing of a hijab, kippah, or turban by some Muslim women, Jewish men, and Sikh men, respectively.…”
Section: Definitions Conceptualizations and Gapsmentioning
confidence: 99%
“…Identity is core to diversity in the workplace reflecting fundamental social differences among people. Workplace diversity entails more than visible or surface-level diversity (e.g., age or ethnicity), but also the deep-level diversity associated with sexual orientation, class, or, indeed, religion (e.g., Ghumman, Ryan, & Park, 2016;Harris & Yancey, 2017).…”
Section: Religious Identity and Workplace Diversitymentioning
confidence: 99%
See 1 more Smart Citation